Desain, Sintesis Dan Uji Sitotoksitas analog UK-3A: Hidroksipikolinil Dioktil Glutamat Ester - YULIA ANITA; MUHAMMAD HANAFI (JURNAL ILMU KEFARMASIAN INDONESIA, 2011)
Antibiotic UK 3A had been isolated as a minor component from the mycelium of Streptomyces sp. 517-0. It was elucidated as a nine-member dilactone ring derivative. To produce an analog of UK-3A, i.e. hydroxypicolinil dioctyl glutamic ester, was synthesized from L glutamic acid and octanol, and the product was then reacted with 3-hydroxypicolinic acid and dioctyl glutamic ester. The tinal product was identified by 1H and 13C FT NMR, FT-IR spectrophotometry, and LC-MS. The it was tested for cytotoxic activity against P388 Murine Leukemia cells. The results showed that the 3-hydroxypicolinyl dioctyl glutamic ester has higher inhibition activity against P388 leukemia cells with IC50 value of 9.80 µg/mL than the activity of UK 3A with IC50 value of 38.4 µg/mL.